The taxonomic identity of Bauhinia bassacensis var. nicobarica (Leguminosae: Caesalpinioideae) - Bandyopadhyay, Subir (Phytotaxa, 2014)
Bauhinia bassacensis var. nicobarica has been treated here as a synonym of Phanera bassacensis.